Learning in Encounter and Addressing Normativity in Religious Education Faculties/Programs - Kock, Jos de (Religious education, 2020)
Working with normative considerations is an important part of empirical research in religious education (RE) and in the formation of practical theologians, in general, and of religious educators in RE faculties/programs, in particular. What does sufficient reflection on normativity look like in teaching religious educators? From a practical theological perspective, directions for working with normativity in RE faculties/programs are provided and discussed. These directions entail pedagogical and theological reflection on the levels of four layers of normativity: (1) discourse in religious practice, (2) the professional theory of practice, (3) the academic theory of practice, and (4) the metatheoretical foundation of observations of and research in practices. The author illustrates the argument with a discussion of the concept of learning in encounter.